Pengaruh Strategi Pembelajaran Matematika Realistik Kontekstual dan Motivasi Belajar Terhadap Hasil Belajar Siswa SD - Siti Munawaroh; Cecep Anwar Hadi Firdos Santosa; Endang Wahyuningrum (Universitas Sarjanawiyata Tamansiswa, 2020)
Realistic mathematics learning strategies are more focused on student learning activities, which Â then connected to studentâ€™s real world daily lives so that the learn process is felt to be more concrete. The purpose of this study is to find out whether realistic mathematics learning strategies and learning motivation have an effect on student mathematics learning outcomes. This research was conducted in fifth grade elementary school students using 2x2 factorial design. The statistical test used was two-way Anova. Based on the results of data analysis with two-way Anova test, it was found that there are differences in students' mathematics learning outcomes. It can be seen from the acquisition of the average value of the two research classes that is equal to 77.81 for experimental class 1 and equal to 61.25 for experimental class 2. However there is no interaction between realistic mathematics learning strategies and learning motivation. This can be seen from the calculated F value < F table that is equal to 0.03 < 3.34.